Applicability of DLC and WC/C low friction coatings on Al2O3/TiCN mixed ceramic cutting tools for dry machining of hardened 52100 steel. Issue 8 (1st June 2020) - Sateesh Kumar, Ch; Majumder, Himadri; Khan, Akhtar; Patel, Saroj Kumar
Abstract: The present work examines the applicability of DLC and WC/C low friction coatings on Al2 O3 /TiCN based mixed ceramic cutting tools for the dry and hard turning of AISI 52100 steel (62 HRC). The characterization of coated tools reveals that the coatings retain very low values of surface roughness, whereas the DLC coating exhibits much higher microhardness when compared to the WC/C coating. On the other hand, the WC/C coating exhibit a coarse surface morphology virtually due to the tungsten doping. Later, continuous turning tests were executed with the help of coated and uncoated cutting tools under dry cutting conditions, and their performance was investigated in terms of machining forces, cutting temperature and tool wear. Coating delamination by flaking and peeling is quite prominent in the case of both the coatings; however, it is less severe for the WC/C coated tool. The coatings help to reduce machining forces, cutting temperatures and tool wear, but the performance of coated tools converge towards uncoated tool as the cutting speed, and feed rate is increased. Both the coatings prevent the development of cracks near the cutting edge with WC/C coating exhibiting superior wear behavior basically due to its multilayered structure and better thermal stability. Moreover, the tested low friction coatings don't serve as thermal barriers and only the lubrication generated due to graphitization at the chip-tool interface is mostly responsible for the improved machining performance.